A study on knowledge, decision-making and acceptance of human papilloma virus vaccination among parents of primary school students in Kota Bharu - Sopian, Mastura Mohd (2016)
Introduction: Human Papilloma Virus Vaccine plays an important role in HPV related illness prevention. Cervical cancer is the second most common cancer in women and forth most common cancer in the entire general population in Malaysia. The primary prevention, HPV vaccine is approved as national vaccination program for females in Malaysia. Children rely on parents not only for the consent but for the guidance and information about the vaccines. Objectives: The study aims to describe knowledge, decision-making and acceptance of Human Papillomavirus (HPV) vaccination among parents of Primary School students and its associated factors. Methodology: This cross sectional study was conducted among 280 parents of primary school students in Kota Bharu from January 2015 till May 2015. Systemic random sampling and a validated self-administered questionnaire was used to assess knowledge of HPV vaccination. Data was analysed using SPSS ver 22. Result: Proportion of good knowledge among parents in Kota Bharu was 38%. Most decision regarding vaccination was a shared decision, 72%. The proportion ofacceptance of HPV vaccine for girls was 63%. Age and knowledge show significant association with HPV vaccine acceptance. Parents with good level of knowledge were more likely to accept HPV vaccine. Conclusion: Majority of parents had poor knowledge of HPV vaccine despite the implementation of the HPV vaccine since 2010. Vaccine acceptance is dependent on the level of knowledge. Parents play an important role in determining the success of HPV vaccine program. The trend of decision-making has changed in Malaysian family as most couples make shared decisions in allowing vaccinations on their child as compared to traditionally decision making by father.